(untitled) (Research, Society and Development, 2021)
This essay analyzes the directed study as a teaching strategy for Professional and Technological Education (EFA), pointing singularities, effects on the teaching-learning process and procedures for its implementation. Constituted in a qualitative and dialectical approach, it was produced following the exploratory and descriptive research types through bibliographic research concentrated in works by authors such as Anastasiou and Alves (2015), Araujo (n.d.), Bordenave and Pereira (2014), Kuenzer (2014), Libâneo (2018), Machado (2008), Nérici (1992), Piletti (2010), Veiga (2017), among others. Because it is an extensive theme, the production focused on the following questions: a) what singularities can be pointed out in the directed study as a teaching strategy in EFA? b) what are the effects of the directed study in the teaching-learning process of EFA? c) how to plan the directed study to be applied in EFA? and d) what procedures are necessary to implement the directed study in EFA? The repercussions of the work indicate that directed study is a strategy that can be employed in EFA, contributing to innovate the teaching-learning process, favoring the development of a pedagogy in which the student is the center of activities, developing themes of his interest, learning to learn, discovering the pleasure of learning, and being the subject of his actions.